STRUKTUR KEPEMILIKAN DAN PENGAMBILAN RISIKO BANK - Rahmat Setiawan; Windy Priga Oktini; Abdul Malik Akmal (LPSDI Bina Patria, 2025)
The purpose of this research is to examine the influence of ownership structure on bank risk-taking in the Indonesian banking industry. This study uses a multiple linear regression model with data from 2012 to 2016. The independent variables are bank ownership (private and government) and ownership concentration (concentrated and non-concentrated). The dependent variable is bank risk-taking measured by credit risk (NPL) and insolvency risk (1/ZSCORE). The results show that bank ownership has a significant negative effect on risk-taking, while ownership concentration has a significant positive effect